2012
DOI: 10.1111/j.1365-2265.2011.04323.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyrotropinemia at 2 weeks of age indicates thyroid dysfunction and predicts the occurrence of delayed elevation of thyrotropin in very low birth weight infants

Abstract: Thyrotropin-releasing hormone stimulation tests at about 2 weeks of age suggested that the hypothalamic-pituitary-thyroid axis might be established even in extremely premature infants. Basal increased TSH levels (TSH > 10 mU/l) and a hyperresponse to TRH stimulation tests (peak TSH > 45 mU/l) suggested subclinical thyroid dysfunction. Serum TSH values at about 2 weeks of age could be useful for the prediction of delayed TSH elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…19 Niwa also adds that the hypothalamicepituitary axis in LBW infants, develops at the age of about 2 weeks, therefore, this age is recommended to be the most suitable time for repetition of the screening test. 36 Considering the studies mentioned above and this systematic review of previous studies, two weeks seems to be the best age to perform the screening test, as the hypothalamicepituitary axis development is initiated at this age and the remaining maternal T4 disappears. It is recommended that the treatment start as soon as the diagnosis of CH is confirmed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…19 Niwa also adds that the hypothalamicepituitary axis in LBW infants, develops at the age of about 2 weeks, therefore, this age is recommended to be the most suitable time for repetition of the screening test. 36 Considering the studies mentioned above and this systematic review of previous studies, two weeks seems to be the best age to perform the screening test, as the hypothalamicepituitary axis development is initiated at this age and the remaining maternal T4 disappears. It is recommended that the treatment start as soon as the diagnosis of CH is confirmed.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, a cutoff level of 10 mU/L can improve the screening test for congenital hypothyroidism, whether in full-term or preterm infants. 36 Another suggested approach is a repetition of the screening test in order to find cases with delayed TSH rise that were missed using the primary test. However, the most suitable time for the 2nd test is disputed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated not only basal‐free thyroxine (FT4) and TSH levels but also TRH stimulation tests, which are helpful in defining thyroid dysfunction in older children and full‐term neonates 27‐29 . In preterm neonates, we previously reported that the hypothalamic‐pituitary‐‐thyroid (HPT) axis could respond to TRH stimulation tests appropriately even in very low birthweight neonates born at < 30 weeks of gestation at about 2 weeks after birth 30 . Therefore, we consider that TRH stimulation tests are helpful for defining thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines of the American Academy of Pediatrics on newborn screening and treatment of CH define all newborns presenting with TSH serum levels persistently higher than 10 mU/L as affected by CH and requiring treatment (1). Niwa et al (11) have shown that hyperthyrotropinemia (TSH>10 mU/L) is a marker of thyroid dysfunction in premature infants aged two weeks or older. However, there is no consensus on treatment of persistent hyperthyrotropinemia with TSH levels between 5 and 10 mU/L.…”
Section: Introductionmentioning
confidence: 99%